CHARACTERISTICS OF SLEEP DISORDERS IN PATIENTS WITH GENERALIZED ANXIETY DISORDER TREATED INPATIENTS AT INSTITUTE OF MENTAL HEALTH, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the characteristics of sleep disorders in patients with generalized anxiety disorder treated inpatients at the Institute of Mental Health, Bach Mai Hospital.Subjects and methods: This cross-sectional descriptive study on 105 inpatients at the Institute of Mental Health, Bach Mai Hospital, diagnosed with generalized anxiety disorder according to ICD-10, aimed to describe the clinical characteristics of sleep disorders in this patient population.Results: 85.7% of the study subjects had sleep disorders. Most sleep disorders appeared before obvious anxiety symptoms (67.8%). Considering the duration of sleep disorders before hospitalization, the number of sleep disorders was over 3 months with 52.2%. Regarding the number of nights of sleep disorders per week, most of the study subjects had 5 nights/week, accounting for 44.4%. Among the types of insomnia, insomnia at the beginning of sleep had the highest rate at 93.3%, followed by difficulty maintaining sleep at 74.4%. A patient can have 1, 2 or 3 types of insomnia, of which the rate of 3 types of insomnia was the highest at 42.2%. According to the ISI scale, moderate insomnia accounts for the highest percentage at 52.2%, followed by mild insomnia at 27.8%. Insomnia mostly affects the quality of work during the day with moderate insomnia accounting for the majority at 56.7%, and up to 31.1% at severe insomnia leading to inability to do work.Conclusions: Sleep disorders are common in patients with generalized anxiety disorder. Patients with generalized anxiety disorder may have 1, 2 or all 3 types of insomnia, of which onset insomnia is the most common type. Insomnia has a great impact on work, in research the level of impact on the quality of daily work with low, moderate and severe levels leading to inability to do work.
Keywords: Sleep disorders, generalized anxiety disorder.